Oncological Outcomes After Hippocampus-Sparing Whole-Brain Radiotherapy in Cancer Patients With Newly Diagnosed Brain Oligometastases: A Single-Arm Prospective Observational Cohort Study in Taiwan - Lin, Shinn-Yn; Tsan, Din-Li; Chuang, Chi-Cheng; Yang, Chi-Cheng; Pai, Ping-Ching; Wang, Chih-Liang; Wu, Yi-Ming; Lee, Cheng-Chi; Lin, Chia-Hsin; Wei, Kuo-Chen; Chou, Wen-Chi (Frontiers in Oncology, 2022)
Background: Promisingly the technique of hippocampus sparing during WBRT(HS-WBRT) might preserve NCFs. In this research, we examined oncological outcomes, with emphasis on neurologic/non-neurologic causes of death, CNS progression, and leptomeningeal disease (LMD) recurrence in cancer patients who underwent HS-WBRT. Methods: One hundred and fourteen cancer patients with newly-diagnosed brain oligometastases underwent HS-WBRT were consecutively enrolled. The cumulative incidence of cancer-specific deaths (neurologic or non-neurologic), LMD recurrence, and the composite endpoint of CNS progression (CNS-CE) as the first event were computed with a competing-risks approach to characterize the oncological outcomes after HS-WBRT. Results: Patients with intact brain metastases had a significantly increased likelihood of dying from non-neurologic death associated with early manifestation of progressive systemic disease (Hazard Ratio for non-neurologic death, 1.78; 95% CI, 1.08 – 2.95; p = 0.025; competing-risks Fine-Gray regression), which reciprocally rendered them unlikely to encounter LMD recurrence or any pattern of CNS progression (HR for CNS-CE as the first event, 0.13; 95% CI, 0.02 – 0.97; p = 0.047; competing-risks Fine-Gray regression). By contrast, patients with resection cavities post craniotomy had reciprocally increased likelihood of CNS progression which might be associated with neurologic death eventually. Conclusions: Patterns of oncological endpoints including neurologic /non-neurologic death and cumulative incidence of CNS progression manifesting as LMD recurrence are clearly clarified and contrasted between patients with intact BMs and those with resection cavities, indicating they are clinically distinct subgroups.